Efficient and tunable purely organic room temperature phosphorescence films from selenium-containing emitters achieved by structural isomerism. Issue 13 (7th March 2022) - Wang, Shuai; Cheng, Zhiqiang; Han, Xianchao; Shu, Haiyang; Wu, Xiaofu; Tong, Hui; Wang, Lixiang
Abstract : The organic emitters based on 9 H -selenoxanthen-9-one can realize fluorescent-to-phosphorescent transformation at room temperature by structural isomerism, and the room temperature phosphorescence quantum yield of the doped film is up to 66.7%. Abstract : Metal-free purely organic room temperature phosphorescent (RTP) materials that can exhibit high RTP efficiencies in film states are highly desired. Herein, we report three donor–acceptor isomers (1, 2, and 3 ) based on a 9-phenyl-9 H -carbazole donor and a 9 H -selenoxanthen-9-one acceptor unit, which show phosphorescent emission in doped films. The substitution position of the donor unit on the 9 H -selenoxanthen-9-one acceptor unit can significantly impact their photophysical properties. In the doped film state, 1 and 2 show bright blue and green RTP with high phosphorescent quantum yields of up to 66.7%, while 3 only exhibits weak fluorescence emission at room temperature and yellow phosphorescence at cryogenic temperature. Through both photophysical and theoretical investigations, effective regulation of the non-radiative transition process of their lowest-lying triplet excited states by isomerization engineering was identified as the origin of their different light-emitting behaviors. Moreover, a 2 -based phosphorescent film sensor for trace oxygen detection is fabricated, which exhibits a wide detection range (0–2.1 × 10 5 ppm), high quenching constant (2.22 × 10 −4 ppm −1 ), and low detection limit (2.8 ppm), demonstrating their application potential as visual sensory materials.